Challenges while Implementing an Energy Management System in a Refractory Industry - Lazarevska A. M., Gjurchinoski Z., Tuneski A. (University of Niš, Faculty of Mechanical Engineering in Niš, 2017)
The main feature of the Energy Management System (EnMS) is to reduce energy usage without affecting product quality, comfort or safety. As such, EnMS offers three main areas where energy savings can be achieved: in processes, in equipment and in modifying employee’s behavior, i.e. in people. Although often neglected, the last area holds the biggest potential for low- or no-cost savings. Therefore, the main focus of this paper sets on energy savings through modifying employee’s behavior, since, in order to achieve expected energy savings, each company must have a committed, trained, and competent personal willing to change their behavior towards a more energy efficient direction. This paper elaborates on the challenges and benefits that arose during implementing the EnMS in line with ISO 50001, in a refractories manufacturing company, which already has implemented and is certified for ISO 9001 and ISO 14001. Via implementing the EnMS, even in a period of only one year, Vardar Dolomit achieved both energy and non-energy benefits. This paper covers learnt lessons and experiences that derived during identifying barriers and corresponding overcoming solutions.
Keywords: management system, energy efficiency, energy policy, driver-barrier analysis